A microtubule polymerase is required for microtubule orientation and dendrite pruning in Drosophila. (8th April 2020) - Tang, Quan; Rui, Menglong; Bu, Shufeng; Wang, Yan; Chew, Liang Yuh; Yu, Fengwei
Abstract: Drosophila class IV ddaC neurons selectively prune all larval dendrites to refine the nervous system during metamorphosis. During dendrite pruning, severing of proximal dendrites is preceded by local microtubule (MT) disassembly. Here, we identify an unexpected role of Mini spindles (Msps), a conserved MT polymerase, in governing dendrite pruning. Msps associates with another MT‐associated protein TACC, and both stabilize each other in ddaC neurons. Moreover, Msps and TACC are required to orient minus‐end‐out MTs in dendrites. We further show that the functions of msps in dendritic MT orientation and dendrite pruning are antagonized by the kinesin‐13 MT depolymerase Klp10A. Excessive MT depolymerization, which is induced by pharmacological treatment and katanin overexpression, also perturbs dendritic MT orientation and dendrite pruning, phenocopying msps mutants. Thus, we demonstrate that the MT polymerase Msps is required to form dendritic minus‐end‐out MTs and thereby promotes dendrite pruning in Drosophila sensory neurons. Synopsis: This study reveals a new paradigm that a conserved microtubule polymerase Mini spindles (Msps) plays a postmitotic role in dendrite pruning in Drosophila sensory neurons. Unexpectedly, excessive microtubule depolymerization leads to altered microtubule orientation in dendrites and thereby impaired dendrite pruning. Mini spindles (Msps), a conserved microtubule polymerase, plays an unexpected role in governing dendrite pruning in Drosophila dendritic arborization sensory neurons. Msps associates with another microtubule‐associated protein TACC, and both stabilize each other in postmitotic neurons. Msps and TACC regulate the minus‐end‐out microtubule orientation in dendrites independently of JNK pathway. The functions of msps in dendritic microtubule orientation and dendrite pruning are antagonized by the kinesin‐13 microtubule depolymerase Klp10A. Excessive microtubule depolymerization, which is induced by pharmacological treatment and katanin overexpression, also perturbs dendritic MT orientation and dendrite pruning, phenocopying msps mutants. Abstract : Cooperation between the microtubule‐associated proteins Mini spindles (Msps) and TACC reveals a link between formation of minus‐end‐out microtubules and dendritic pruning in Drosophila sensory neurons.